Gaya Komunikasi Guru Besar dan Hubungannya Terhadap Kepuasan Kerja Guru Sekolah Rendah Zon Semenyih Daerah Hulu Langat - Md Yusof, Mohd Nazrul (Selangor Humaniora Review, 2019)
The purpose of this study was to examine the level of head teachers’ communication practices and job satisfaction among primary school teachers in Hulu Langat, Selangor. This study also aimed to identify the influence of teacher demographics such as gender, age, teaching experience and job positions on head teachers’ communication practices and to identify variables that contribute to teacher job satisfaction. The Supervisory Communication Scale (SCS) instrument was used to measure the elements of communication practiced by head teachers such as positive expressions, negative expressions, work orders, job rations, job descriptions, feedback and engagement. While teacher job satisfaction was measured using Brayfield and Rothe's Job Satisfaction Index. 139 trained teachers from 11 primary schools in Hulu Langat district in Selangor were involved as respondents in this study. Sampling was randomly stratified. Data collection was done by using a questionnaire. Descriptive and inferential statistical data analysis was used in this study while Pearson-r Correlation, One Way ANOVA and T-Test were used in the testing of hypotheses. The findings showed that three of the seven communication elements that head teachers often practised were job rationale, engagement and work instructions. Overall, the satisfaction of primary school teachers was moderate. There was a positive relationship between elements of communication practiced by the head teachers and job satisfaction of the teachers. The findings also showed that there was no difference in perspective among teachers towards the head teachers communication practices based on demographic factors such as gender, age, teaching experience and job positions. Hence, the head teachers need to take appropriate action and pay serious attention to their communication practices that could contribute to teacher job satisfaction.